Crosstalk between the osteogenic and neurogenic stem cell niches: how far are they from each other? - Maria Concetta Geloso (Frontiers Research Topics, 2016)
Somatic stem cells reside in definite compartments, known as "niches", within developed organs and tissues, being able to renew themselves, differentiate and ensure tissue maintenance and repair. In contrast with the original dogmatic distinction between renewing and non-renewing tissues, somatic stem cells have been found in almost every human organ, including brain and heart. The adult bone marrow, in particular, houses a complex multifunctional niche comprising hemopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs), that intensely interact. HSCs represent the common precursors of all mature blood cells. MSCs are instead able to differentiate along multiple mesodermal lineages and are believed to represent the key somatic stem cell within the skeletogenic niche, being conceptually able to produce any tissue included within a mature skeletal segment (bone, cartilage, blood vessels, adipose tissue, and supporting connective stroma). Despite this high plasticity, the claim that MSCs could be capable of transdifferentiation along non-mesodermal lineages, including neurons, has been strongly argued. Adult osteogenic and neurogenic niches display wide differences: embryo origin, microenvironment, progenitors' lifespan, lineages of supporting cells. Although similar pathways may be involved, it is hard to believe that the osteogenic and neurogenic lineages can share functional features. The outbreaking research achievements in the field of regenerative medicine, along with the pressing need for effective innovative tools for the treatment of neurodegeneration and neurologic disorders, have been forcing experimental clinical applications, which, despite their scientific weakness, have recently stimulated the public opinion. Based on this contemporary background, this Research Topic wish to provide an in-depth revision of the state of the art on relevant scientific milestones addressing the differences and possible interconnections and overlaps, between the osteogenic and the neurogenic niches. Dissertations on both basic research and clinical aspects, along with ethical and regulatory issues on the use of somatic stem cells for in vivo transplantation, have been covered.